Jual Beli Model âInah di Lembaga Keuangan Syariah: Tinjauan Konsep, Hukum dan Implementasi - Mulyawisdawati, Richa Angkita; Afif, Mufti (Universitas Muhammadiyah Malang, 2018)
The sale and purchase of inah and tawarruq is a classic problem that is recognized or not continues to grow and be practiced by individuals and financial institutions to date. Based on the facts on the ground, this type of engineering of sale and purchase occurs in Islamic Financial Institutions (LKS), where Islamic Financial Institutions only serve and serve financial services for its customers who need funds. So much is found that most LKS activities lead to financing through murabahah scheme where the scheme of the contract is considered safe for the LKS because the level of risk is lower than other types of contract. This paper is intended to determine the nature of the concept and legal sale and purchase inah and tawarruq according to scholars fiqh classics and how the practices of these two transactions became an issue on financial transactions in LKS. By using descriptive qualitative method, literature approach and history, it is produced that the type of sale of Inah and Tawarruq is still debated by the jurists of fiqh jurisprudence and the tendency is forbidden because there is a rift of ribawi transaction in it. While in practice in LKS is still widely applied and growing especially in superior products (murabahah) as in financing business capital, credit card, home financing or home renovation or the like and gold-based financing.